Experimental and numerical analyses on aluminium alloy H-section members under eccentric cyclic loading. (May 2021) - Wu, Jinzhi; Zheng, Jianhua; Sun, Guojun
Abstract: This paper considered the combination of cyclic load and eccentric load to study the hysteretic performance of H-section 6061-T6 aluminium alloy members For this reason, this study designs and conducts the eccentric cyclic loading test of three H-section 6061-T6 aluminium alloy members with different slenderness ratios based on a reliable test system. The failure form, failure process, and bearing capacity of each member are analysed. The results show that for eccentrically loaded members, no overall buckling is observed during loading. Moreover, the members along the longitudinal direction do not fully develop plasticity, whereby such plasticity in the full sections is avoided. Plastic local buckling controls the failure mechanism of all specimens, leading to degradation in the stiffness of the specimens and generation of subsequent cracks at the local buckling sites of the webs, which in turn leads to fracture failure. Simultaneously, on the basis of the Chaboche hybrid strengthening model, the member model was established using the ABAQUS finite element (FE) software. Furthermore, the material parameters were calibrated using material test data and fitted the cyclic constitutive relationship of aluminium alloy. The effectiveness of the FE simulation method and the rationality of the constitutive model was accurately verified by experimental results. Additionally, the parameter analysis of eighteen members with different cross-sections, slenderness ratios, and eccentricities was carried out. It is shown that the increase of slenderness ratio and eccentricity result in weakening of the energy consumption capacity and bearing capacity obviously, which thereby provides a reference for the seismic design of aluminium alloy structures. Highlights: The failure modes of aluminium alloy H-section members under eccentric cyclic loading are analysed by experiments. The hysteretic performance of members is obtained via eighteen numerical analysis models. The definition of cyclic constitutive relationship of 6061-T6 aluminium alloy material are fitted by experiments. The variation rules of bearing capacity of members under eccentric cyclic loading are provided.